Introduction – Veterinary services in a changing world: climate change and other external factors - Grace, Delia; Hu Suk Lee; Smith, Jimmy W. (World Organisation for Animal Health, 2021)
This is the first issue of the Scientific and Technical Review that focuses on Foresight and the broad range of external factors that are likely to affect, and be affected by, Veterinary Services, both in the present and in the near future. The edition is particularly timely, coming at a moment of unprecedented interest in the role of animal agriculture and its relationship with people and the environment.